AN OVERVIEW ABOUT THE USE OF ANTIBIOTIC IN PREGNANCY AND NURSING MOTHER IN MAKASSAR - Darmawansyih Darmawansyih; Nadyah Haruna (Molucca Medica, 2017)
Introduction. Pregnancy is a physiological process that needs to be well prepared due to the correlation from mother and the fetus. By the same token nursing is also alike that all the substances which consumed by the mother will get in to fetal circulation. It can be denied that the condition in our community drug consumption on pregnancies women and nursing whom use drugs and supplements during the period of organogenesis progress will give a high risk of fetal defects and adverse impact to their baby. Aims. For that reasons the aim of this study is to describe the use of antibiotics in pregnancy and nursing mother in the Pertiwi Maternal and Child’s Hospital, Makassar 2014. Methods. This study was descriptive that involve all pregnancies and nursing mothers who use antibiotic are the population. Total sampling as much as 32 pregnancies and 329 nursing mothers who used antibiotics taken from Pertiwi Maternal and Child’s Hospital. Result. Some principal findings from this study are first during pregnancy the main cause that made the pregnancies used antibiotics depending on the illness experienced. Another finding is the most antibiotics that used by the pregnancies are Amoxicillin, Ampicillin and Cefadroxil where some of them bought it by their self without prescription. Another crucial finding is 329 nursing mothers use amoxicillin because of the rupture of the perineum without sensibility test before. Conclusion. This study can be drawn principal that antibiotics are the most widely used and safest when compared with other antibiotics is amoxicillin and ampicillin from the penicillin group. Another conclusion that can be drawn is the use of antibiotics during pregnancy should take into consideration several aspects, circumstances or maternal disease and the possibility of teratogenic drugs.